Impotent Husband Culpable Wife: Feminization of Infertility in Ayobami Adebayo’s Stay with Me - Abianji-Menang, Ophilia A. (Advances in Social Sciences Research Journal, 2024)
This paper examines infertility as a major reproductive health problem that brings shame and leads to social exclusion of women in Sub-Saharan Africa. Infertility is a global issue that affects couples; however, the concept has been institutionalised by the enterprise of patriarchy in Sub-Saharan Africa to make it a woman’s issue. The paper demonstrates how childlessness has been socially and culturally constructed in African societies to hold women responsible for a couples’ problem, irrespective of the male factors related to infertility. The purpose of this paper is to disseminate information on reproductive health, which is a challenging conversation in most African communities, due to the complexity in the subject. Based on Ayobami Adebayo’s novel, Stay with Me, the text explores the task of the postcolonial African literary artist in providing information on infertility (reproductive health) in their narrative, hence, the interrelation between literary discourse and reproductive health. Erving Goffman’s theory of stigma will be employed to portray how childlessness is a discrediting problem in Sub-Saharan Africa. It is a traumatic experience that reduces women to a tainted and discount other. The institution of motherhood created by patriarchy creates stereotypes about childless women for the interest of sterile men. Considering that male and female factors of infertility co-exist, the dialogic approach of Mary E. Modupe Kolawole and Obioma Nnaemeka is necessary in the follow up and management of infertility rather than focus on the woman who may not necessarily be the problem.